INDIVIDUAL SELF-CONFIDENCE IN SOCIAL CONTEXT - Putri, Niky Isoya (Program Studi Bimbingan dan Konseling FKIP UNJA, 2023)
Self-confidence is an attitude or belief in one's own abilities so that one is not too worried about one's actions, feels free to do what one wants and is responsible for one's actions, is polite in dealing with other people, has the desire to achieve and knows one's strengths and weaknesses. Facing the challenges of this era of globalization requires us to continue to develop in all aspects, including our human resources. Quality people can make a country proud in competition on the world stage. This can occur due to several factors, namely educational services and consideration of individual talents, interests, abilities and intelligence. This manifests itself through simple things like fulfilling duties and responsibilities, which includes completing tasks to the best of your ability and setting specific goals and strategies. This literature study aims to determine individual self-confidence in a social context. This literature study also focuses on the problem of individual self-confidence in social interactions